The using of megavoltage computed tomography in image-guided brachytherapy for cervical cancer: A case report - Ekkasit Tharavichitkul (2018)
© 2015. The Korean Society for Radiation Oncology. We present a case of cervical cancer treated by concurrent chemoradiation. In radiation therapy part, the combination of the whole pelvic helical tomotherapy plus image-guided brachytherapy with megavoltage computed tomography of helical tomotherapy was performed. We propose this therapeutic approach could be considered in a curative setting in some problematic situation as our institution.